ANALISIS KARAKTERISTIK DAN TINGKAT PELAYANAN PEJALAN KAKI DI KAWASAN PASAR PAGI KOTA SAMARINDA ( Studi Kasus : Jalan Jend. Sudirman – Jalan Kh. Kholid ) - MUKAROM, MAX (KURVA S JURNAL MAHASISWA, 2018)
Transportation is a movement that can be the movement of people, goods, and information from one place to another safely, comfortably, quickly, and in accordance with the environment to meet the needs of human life. Basically, pedestrian traffic performance is expressed in a manner similar to the expression of vehicle traffic performance with flow, speed, and interconnected density. This study was conducted to determine the characteristics of pedestrians, how the relationship between speed (speed), flow (flow ), density (density), in the region. In addition to know the capacity and Level Of Service (LOS).                Research method in this research use survey method and analysis method. Survey method that is by using manual technique in observation and collecting data in field. From the survey results in the field obtained data on the number of pedestrians, pedestrian travel time and the width of the pedestrian path. While the method of analysis that is by using Greenshields method. based on the magnitude of the current and the amount of pedestrian space (pedestrian) for pedestrians at the largest 5-minute intervals and matched to field conditions.                From the calculation results it is concluded that in segment A has a large current value than the other segments, with currents of 11.6556, 12.1854 and 12.8477 pedestrians / min / m. and space value due to narrowing of lines 1.8193, 1.8534 and 1.5288 m2 / pedestrians in the "D" category shows that pedestrian facilities in the morning market area have not been able to accommodate the number of existing pedestrians. So it is necessary to rearrange the area